Current and future intratumoral targeted treatment for pancreatic cancer. (August 2014) - Zarogoulidis, Paul; Pavlioglou, Paschalis; Pivert, Patrick Le; Machairiotis, Nikolaos; Katsikogiannis, Nikolaos; Kougioumtzi, Ioanna; Tsimogiannis, Konstantinos; Kakolyris, Stylianos; Courcoutsakis, Nikolaos; Tsiouda, Theodora; Sakkas, Antonios; Makrantonaki, Dimitra; et al.
Pancreatic cancer is an insidious type of cancer with its symptoms manifested upon extensive disease. The overall 5-year survival rates between 0.4 and 4%. Surgical resection is an option for only 10% of the patients with pancreatic cancer. Local recurrence and hepatic metastases occur within 2 years after surgery. There are currently several molecular pathways investigated and novel targeted treatments are on the market. However; the nature of pancreatic cancer with its ability to spread locally in the primary site and lymph nodes indicates that further experimentation with local interventional therapies could be a future treatment proposal as palliative care or adjunct to gene therapy and chemotherapy/radiotherapy. In the current review, we will summarize the molecular pathways and present the interventional treatment options for pancreatic cancer.